Greenhouse gas and volatile organic compound emissions of additive-treated whole-plant maize silage: part B—aerobic storage period and carbon footprint of silage additive use - Hauke Ferdinand Deeken; Gerd-Christian Maack; Manfred Trimborn; Wolfgang Büscher (Chemical and Biological Technologies in Agriculture)
Abstract Background Silage emits climate- and environment-relevant gases during anaerobic fermentation and aerobic feed-out periods. This trial should determine the unknown CO2, methane, nitrous oxide, ethanol and ethyl acetate emissions of constant maize silage over both periods. The results will be published in two consecutive articles (Part A: anaerobic fermentation period; Part B: aerobic storage period). Methods Three silage treatments were observed (n = 4): The untreated control (CON) was compared to the chemical additive treatment (CHE; 0.5 g sodium benzoate and 0.3 g potassium sorbate per kg fresh matter) and the biological additive treatment (BIO; 1 × 108 colony-forming units Lentilactobacillus buchneri and 1 × 107 colony-forming units Lactiplantibacillus plantarum per kg fresh matter). During the two aerobic emission measurement periods (AEMP), the silos were ventilated mechanically to supply 2–6 (L air) min–1 to the two faces of the material (150.6 kg dry matter m–3). AEMP1 (duration 14 days) began on ensiling day 30, AEMP2 (19 days) on day 135. Results In AEMP1, aerobic stability differed among the treatments (p < 0.05): 5.17 ± 0.75 days for CON, 6.33 ± 0.15 days for BIO, and 7.33 ± 0.57 days for CHE. In AEMP2, only CON showed a temperature increase of 2 K above ambient temperature after 7.75 ± 0.31 days. BIO and CHE indicated higher ethanol and ethyl acetate emission rates during the first period of the heating process. Furthermore, 20.0%–70.4% of ethanol and 169.0%–953.6% of ethyl acetate quantities present in the material at the silo opening emitted as gases. Conclusion Methane and nitrous oxide emissions during anaerobic fermentation exceeded the quantities during aerobic storage in all treatments. However, compared with those of crop production, the total climate-relevant CO2eq emissions are small. Microbial respiration during heating leads to climate-neutral CO2 emissions and dry matter losses. Minimising these losses is promising for mitigating climate-relevant emissions directly during silage storage and indirectly during crop production since less forage input is needed. Thus, silage additives can help improve the silage carbon footprint by improving aerobic stability and silage deterioration. Graphical Abstract